2019
DOI: 10.12659/msm.914011
|View full text |Cite
|
Sign up to set email alerts
|

H₂O₂ Damages the Stemness of Rat Bone Marrow-Derived Mesenchymal Stem Cells: Developing a “Stemness Loss” Model

Abstract: Background The number of patients with spinal cord injury caused by motor vehicle accidents, violent injuries, and other types of trauma increases year by year, and bone marrow mesenchymal stem cell (BMSC) transplants are being widely investigated to treat this condition. However, the success rate of BMSCs transplants is relatively low due to the presence of oxidative stress in the new microenvironment. Our main goals in the present study were to evaluate the damaging effects of H 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Previous studies have strongly indicated that BMSCs can effectively promote cartilage erosion regeneration in OA by not only differentiating into cartilage-forming chondrocytes but also modulating the behavior of subchondral bone 5 . However, the abnormal microenvironment of OA characterized by stress conditions, such as inflammation 6 and oxidative stress 7 , 8 , reduces the survival capacity of BMSCs. Moreover, high pro-inflammatory cytokine levels inhibit BMSCs osteogenesis 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have strongly indicated that BMSCs can effectively promote cartilage erosion regeneration in OA by not only differentiating into cartilage-forming chondrocytes but also modulating the behavior of subchondral bone 5 . However, the abnormal microenvironment of OA characterized by stress conditions, such as inflammation 6 and oxidative stress 7 , 8 , reduces the survival capacity of BMSCs. Moreover, high pro-inflammatory cytokine levels inhibit BMSCs osteogenesis 9 .…”
Section: Introductionmentioning
confidence: 99%